Engaging the Private Sector in Transport and Logistics Planning and Policy Making : Options for Vietnam - Blancas, Luis C. (World Bank, Washington, DC, 2016)
In the 22 years between 1992 and 2014 Vietnam attained the remarkable average annual rate of economic growth of 6.9 percent. However, the sources of growth that underpinned much of this period of economic transformation ready availability of labor and a structural shift of national production from subsistence agriculture to industry and services are gradually being depleted and cannot be sustained indefinitely. Given that a substantial share of Vietnam’s growth has been associated with the expansion of manufacturing linked to international trade, more competitive freight logistics which are the backbone of import-export activity should be among those levers. This report aims to compile the key lessons that have been learned by other countries in setting up platforms for direct dialogue between public sector agencies and private sector freight stakeholders at the planning and policy making level. This experience yields options for Vietnam to strengthen its own approaches to public private and public policy dialogue in logistics. Chapter one gives background and current situation. Chapter two briefly summarizes the current state of private sector involvement in the public sector functions of management and oversight of Vietnam’s logistics industry. Chapter three draws lessons from a limited number of relevant countries where governments have instituted institutional mechanisms for private sector engagement and inter-agency collaboration in logistics and transport planning and policy making. Chapter four offers recommendations for the Government of Vietnam (GoV) towards realistically implementing and ultimately mainstreaming robust private sector engagement and inter-agency collaboration in logistics. Chapter five presents the findings of a recent World Bank- Ministry of Transport (MoT) survey of Vietnam-based private sector freight stakeholders on the subject of private sector engagement in the planning and policy making processes of government. Chapter six concludes by offering examples of the kinds of good public sector logistics management practices that the GoV can pursue if it availed itself of the collaborative mechanisms recommended by this report.